Determination of the Sensitivity and Specificity of Serum Prostate-Specific Antigen in the Diagnosis of Prostrate Cancer in Kano, Northwestern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Early detection is an essential step in decreasing the mortality and morbidity related to prostate cancer. Serum prostate-specific antigen (PSA) testing is a proven effective tool for early detection of prostate cancer. It has high sensitivity but low specificity and remains an important screening tool.Objectives:This study aims at finding a local reference sensitivity and specificity level of serum PSA in Kano, Northwestern Nigeria.Materials and Methods:A cross-sectional descriptive study of 93 patients who had lower urinary tract symptoms and digital rectal examination (DRE) findings suggestive of cancer of the prostate and/or raised PSA who presented to urology outpatient clinic of Aminu Kano Teaching Hospital, Kano over the period of one year (January to December 2012). All patients had transrectal ultrasound-guided biopsy for histological evaluation. The sensitivity and specificity of PSA were then analysed.Results:A total of 93 patients participated in the study with age range from 50 to 96 years and mean age of 68.086 ± 9.368 years. The sensitivity of PSA was found to be 91.4% but dropped to 47.3 when the reference ranged were considered at 0–4.0 ng/ml and 0–10.0 ng/ml, respectively. Also, the specificity was found to be 22.4% but raised to 77.0% at the other reference range. The diagnostic accuracies for 0–4 and 4.1–10 ng/ml were 48.0% and 59.1%, respectively.Conclusions:PSA testing still has a role to play in the diagnostic pathway and is relatively non-invasive, inexpensive with a high sensitivity. However, it has a low specificity. The reference range in our environment remains the international range of 0–4 ng/ml.